2002
DOI: 10.4238/2002.march.30.8
|View full text |Cite
|
Sign up to set email alerts
|

Further phenotypic characterization of pso mutants of Saccharomyces cerevisiae with respect to DNA repair and response to oxidative stress

Abstract: cox11-∆ exhibited additivity of 8HQ and NDEA sensitivities of the single mutants, indicating that two different repair/recovery systems are involved in survival. DEO sensitivity of the double mutant was equal or less than that of the single snm1-∆ mutant. In order to determine if there was oxidative damage to nucleotide bases by these drugs we employed an established bacterial test with and without metabolic activation. After S9-mix biotransformation, NDEA and to a lesser extent 8HQ, lead to significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…It should be noticed that pso6/erg3 mutants were also sensitive to NDEA, but not to 8HQ, most probably due to the inability of 8HQ to cause LP [103].…”
Section: Pso Genes That Are Involved In Mutagen Metabolism and Not Inmentioning
confidence: 96%
See 1 more Smart Citation
“…It should be noticed that pso6/erg3 mutants were also sensitive to NDEA, but not to 8HQ, most probably due to the inability of 8HQ to cause LP [103].…”
Section: Pso Genes That Are Involved In Mutagen Metabolism and Not Inmentioning
confidence: 96%
“…Repair-proficient pso7/cox11 mutants were found highly sensitive to the mutagens NDEA, an alkylating chemical that is metabolized via redox cycling to yield hydroxylamine radicals, ROS and LP [88,101,102] and to 8-hydroxyquinoline (8HQ), which may also be activated via altered oxygen metabolism [103] and possibly form diol-epoxide derivatives [104,105]. It should be noticed that pso6/erg3 mutants were also sensitive to NDEA, but not to 8HQ, most probably due to the inability of 8HQ to cause LP [103].…”
Section: Pso Genes That Are Involved In Mutagen Metabolism and Not Inmentioning
confidence: 99%
“…The absence of the protein codified by that gene leads to specific responses described as phenotypes [12] that characterize the metabolic pathway in which it is involved, i.e., mutants in proteins involved in DNA repair are more sensitive to drugs that cause DNA damage that is repaired by that biological pathway. Therefore, this is a very powerful system to rapidly identify a putative mechanism of drug action in a complex cell [13]. Here we used a set of 10 yeast null mutants involved in DNA repair, representing the three so-called epistasis groups, which are thought to reflect three major DNA repair pathways: RAD3 (involved in nucleotide excision repair [NER], Figure 2A), RAD52 (recombinational repair, Figure 2B) and RAD6 (error-prone repair, Figure 2C) epistasis group genes [14–16]; 3 yeast mutants defective in membrane composition or transport across the membrane (Figure 2D); and 3 yeast mutants defective in oxidative stress protection mechanisms (Figure 2E).…”
Section: Resultsmentioning
confidence: 99%
“…The higher than wild-type sensitivity to pso2 Δ ( snm1 Δ) (Figure 2B) suggested that some substance of CaRP might intercalate with DNA and induce lesions that link the two DNA strands. Evidence of this comes from some studies that showed pso2 Δ mutant specifically blocked in repair of interstrand cross-links [13]. These results could be promising because many antitumoral drugs act by intercalating into DNA and forming interstrand cross-links, e.g., photoactivated psoralens, mitomycin C and cis -platinum [17].…”
Section: Resultsmentioning
confidence: 99%